Methodical Appraisal Aspects of the Financial Risk of Investiments - Aleknevičienė, Vilija (Ekonomika, 1997)
The determinants of financial risk are fixed and variable financing costs, so this type of risk bear only the equity holders nf geared enterprise. There are a lot of appraisal techniques and measures of financial risk: financial gearing ratio, interest cover ratio, fixed costs cover ratio, effect of financial gearing, degree of financial gearing, and indifference analysis and financial indifference point. All their measures make no sense, if historical data are not compared with forecasting results. This, however, is not sufficient. The theory of capital structure gives very little griedance to managers, so the safest thing to do is to do what everybody else does; thus, one of the most important considerations in capital structure decisions in the real world will be what the average level of gearing, earnings per share, and interest cover ratio for the industrial group will be. Enterprises will tend to be rather cautious about moving their financial risk indicators too far away from their average levels of industry. Enterprises must be interested in gathering such information in order to more easily make financial risk management decisions.